1999
DOI: 10.1046/j.1365-313x.1999.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐organ signaling in plants: regulation of ATP sulfurylase and sulfate transporter genes expression in roots mediated by phloem‐translocated compound

Abstract: SummarySulfate uptake and ATP sulfurylase activity in the roots of Arabidopsis thaliana and Brassica napus were enhanced by S deprivation and reduced following resupply of SO 4 2-. Similar responses occurred in split-root experiments where only a portion of the root system was S-deprived, suggesting that the regulation involves inter-organ signaling. Phloem-translocated glutathione (GSH) was identified as the likely transducing molecule responsible for regulating SO 4 2-uptake rate and ATP sulfurylase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
175
4
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(188 citation statements)
references
References 33 publications
5
175
4
4
Order By: Relevance
“…34 It has been reported that withdrawal of S from the medium leads to decreased levels of sulfate and GSH in Arabidopsis and canola plants tissues resulting in the induction of sulfate transporter systems and ATPS activity. 35,36 The inhibition in the activity of ATPS1 and APR results in the inhibition of GSH synthesis. 37,38,39 Supplementation of 0.5 mM SA results in the substantial increase in ATP sulfurylase, serine acetyl transferase activity and Cys content under salt stress and helps in reversing the effects of NaCl ¡ induced ROS on photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…34 It has been reported that withdrawal of S from the medium leads to decreased levels of sulfate and GSH in Arabidopsis and canola plants tissues resulting in the induction of sulfate transporter systems and ATPS activity. 35,36 The inhibition in the activity of ATPS1 and APR results in the inhibition of GSH synthesis. 37,38,39 Supplementation of 0.5 mM SA results in the substantial increase in ATP sulfurylase, serine acetyl transferase activity and Cys content under salt stress and helps in reversing the effects of NaCl ¡ induced ROS on photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…1B). The phylogenic relationships of plant sulfate transporters indicated that Sultr1;3 falls into the group of highaffinity sulfate transporters in the vascular plants (Smith et al, 1995(Smith et al, , 1997Vidmar et al, 1999;Takahashi et al, 2000;Shibagaki et al, 2002;Yoshimoto et al, 2002;Fig. 2).…”
Section: Identification Of a Novel High-affinity Sulfate Transportermentioning
confidence: 99%
“…Glutathione and S-methyl-Met are the major sulfur compounds in the phloem sap (Bourgis et al, 1999). Furthermore, glutathione translocated in the phloem is suggested to mediate transmission of the interorgan signal of sulfur status in vascular plants (Lappartient et al, 1999). Studies with poplar more recently suggested a correlation between the demand of sulfur in shoots and the sulfate to glutathione ratio in the phloem sap (Herschbach et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous application of GSH downregulated expression of a sulfur transporter gene Sultr2;2, and a gene encoding ATP sulfurylase (Lappartient et al 1999). Exogenous application of OAS resulted in upregulation of expression of genes encoding adenosine 5Ј-phosphosulfate reductase, chloroplastic and cytosolic cysteine synthase and serine acetyltransferase (Koprivova et al 2000).…”
mentioning
confidence: 99%